A chemical tool for blue light-inducible proximity photo-crosslinking in live cells. Issue 4 (22nd December 2021) - Mishra, Pratyush Kumar; Kang, Myeong-Gyun; Lee, Hakbong; Kim, Seungjoon; Choi, Subin; Sharma, Nirmali; Park, Cheol-Min; Ko, Jaewon; Lee, Changwook; Seo, Jeong Kon; Rhee, Hyun-Woo
Abstract : We developed a spatiotemporal proximity photo-crosslinking by visible light activation ( Spotlight ) method to capture protein–protein interactions in live systems. Abstract : We developed a proximity photo-crosslinking method ( Spotlight ) with a 4-azido- N -ethyl-1, 8-naphthalimide (AzNP) moiety that can be converted to reactive aryl nitrene species using ambient blue light-emitting diode light. Using an AzNP-conjugated HaloTag ligand (VL1), blue light-induced photo-crosslinked products of various HaloTag-conjugated proteins of interest were detected in subcellular spaces in live cells. Chemical or heat stress-induced dynamic changes in the proteome were also detected, and photo-crosslinking in the mouse brain tissue was enabled. Using Spotlight, we further identified the host interactome of SARS-CoV-2 nucleocapsid (N) protein, which is essential for viral genome assembly. Mass analysis of the VL1-crosslinked product of N -HaloTag in HEK293T cells showed that RNA-binding proteins in stress granules were exclusively enriched in the cross-linked samples. These results tell that our method can reveal the interactome of protein of interest within a short distance in live cells.